Kreativitas Sutradara Dalam Pembuatan Iklan Komersial Produk Ronas Di PT Revass Utama Medika - Adrian, Adrian; Ika Sartika; Fikry Fahrurrizal (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Visual communication plays a vital role in advertising, particularly in delivering product messages in an engaging and effective manner. In this context, the director holds a crucial role in shaping the success of an advertisement through creative and strategic visual concepts. This paper discusses a commercial advertisement project for Ronas, a Korean skincare brand distributed by PT Revass Utama Medika. The author applied the 5C concept (camera angle, continuity, cutting, composition, and close-up) as a visual approach to enhance the quality and appeal of the product message. This project serves not only as an implementation of the knowledge gained during studies at the Digital Communication and Media Study Program, Vocational School of IPB University, but also as an exploration of creativity in directing visual-based advertisements. The results of this project demonstrate that the director’s creativity significantly contributes to building a product’s image and influencing consumer decisions through informative, emotional, and persuasive visual storytelling.